The association between denture use and cardiovascular diseases. The United States National Health and Nutrition Examination Survey 2009–2018 - Liang, Xiaopeng; Chou, Oscar Hou In; Cheung, Bernard M. Y. (Frontiers in Cardiovascular Medicine, 2023)
Introduction: Poor dental health is associated with cardiovascular diseases (CVD). However, the relationship between CVD and denture use is currently unknown. This study aimed to investigate whether denture use is associated with CVD among American adults. Methods: 10246 non-pregnant subjects aged 30-59 years from five cycles (2009-2018) of the United States National Health and Nutrition Examination Survey (NHANES) were included in this study. Participants who were observed by a dental examiner wearing denture/partial denture/plates were defined as denture users. CVD was defined as self-reported coronary heart disease, myocardial infarction, angina pectoris, stroke, and congestive heart failure. The association between denture use and CVD was analyzed using logistic regression with adjustment for potential cofounders. Results: 4.4% (95% CI, 3.9-5.0) participants had CVD, and 3.5% (95% CI, 2.8-4.5) participants were recommended or already using dentures. Denture use was associated with CVD [OR=4.26, 95% CI (2.90-6.28), P<0.01], which remained significant [adjusted OR=1.82, 95% CI (1.15-2.88), P<0.01] after adjustments for sociodemographic characteristics, smoking, alcohol use, drug addiction, body mass index and abnormal medical conditions including gum problem, hypertension, diabetes, and hyperlipidemia. Women with dentures had significantly higher odds of CVD [adjusted OR=2.13, 95% CI (1.10-4.11), P=0.025]. Conclusions: In this nationally representative survey, denture use was associated with CVD. Denture use may be an unconventional risk factor for assessing CVD risks, especially in women. Future studies are required to investigate whether CVD and denture use is causally related.